The impact of gold and oil prices on ASEAN’s financial sustainability before and during COVID-19 pandemic - Kok Sook Ching; Caroline Geetha, Wilson Vun Chiong (Penerbit Universiti Malaysia Sabah, 2025)
This study investigates the impacts of gold and oil prices on ASEAN’s financial sustainability before and during the COVID-19 pandemic. The financial sustainability of the ASEAN economics was measured using the performance in the stock market. Among the ASEAN countries, 8 countries produce oil meanwhile 5 countries produce gold. The study used panel data analysis to measure the impact of gold and oil prices on stock market performance. Since there are 3 countries in ASEAN that neither produces gold nor oil but only consumes them, other macroeconomic variables like gross domestic product, exchange rate and inflation rate were added in the analysis as the independent variables together with oil and gold prices. The study was also further distinguished into before the pandemic (2012 – 2019) and during the pandemic (2020 – 2021). The analysis revealed from the random effect regression that oil price and inflation rate influenced the stock performance before and during the pandemic. Both the variables moved in the same direction with stock performance. All other variables were found to be insignificant.